LIGHT CHILD WORK IN INTERNATIONAL STANDARDS AND COMPARATIVE PRACTICE - Jašarević, Senad; Božičić, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The protection of children at work was one of the first topics addressed by labor legislation in the world. However, the regulation of child labor remains one of the insufficiently regulated areas in labor law. Within that, one of the newer topics is light work of children. This form of child labor has existed since time immemorial, especially in the family and household, so it is considered useful for acquiring work habits and experience. However, it can be both dangerous and harmful. In this paper, we present the light work topic, with an emphasis on the existing regulations in the world and the possibilities for a best solutions for regulation of this form of work.